MASS TRANSFER IN ECLIPSING BINARY STARS - V. G. Karetnikov; E. V. Menchenkova; V. V. Nazarenko (Odessa Astronomical Publications, 2017)
Analysis of the properties of the eclipsing binary stars shows, that the stream-like mechanism of the mass transfer switches on at a contact evolutionary stage, preceding to a stage of binaries with a subgiant. The computations of the gas streams near the inner Lagrangian point have been made for the intermediate-mass contact systems of the early spectral classes (CE - systems). The properties of the streams are discussed and the conclusions are done concerning the evolutionary stage of the stars of this type.